2018
DOI: 10.1049/iet-bmt.2017.0050
|View full text |Cite
|
Sign up to set email alerts
|

Human‐level face verification with intra‐personal factor analysis and deep face representation

Abstract: The last two decades have seen an escalating interest in methods for large-scale unconstrained face recognition. While the promise of computer vision systems to efficiently and accurately verify and identify faces in naturally occurring circumstances still remains elusive, recent advances in deep learning are taking us closer to human-level recognition. In this study, the authors propose a new paradigm which employs deep features in a feature extractor and intra-personal factor analysis as a recogniser. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, the potential of computer vision algorithms to efficiently, reliably, and accurately identify human faces in naturally occurring circumstances still remains elusive. Recent trends in deep learning are taking us closer to human-level recognition [39]- [40]. In this study, we empirically observed that deep learning based face recognition algorithm [39], on high image resolutions, such as 80×80 pixels and above outperforms compared algorithms on the LFW and Multi-PIE databases for pose variation and under non-uniform illuminations.…”
Section: Discussionmentioning
confidence: 74%
“…However, the potential of computer vision algorithms to efficiently, reliably, and accurately identify human faces in naturally occurring circumstances still remains elusive. Recent trends in deep learning are taking us closer to human-level recognition [39]- [40]. In this study, we empirically observed that deep learning based face recognition algorithm [39], on high image resolutions, such as 80×80 pixels and above outperforms compared algorithms on the LFW and Multi-PIE databases for pose variation and under non-uniform illuminations.…”
Section: Discussionmentioning
confidence: 74%
“…Craig (1995), detailed that individuals who hold negative assessments about themselves utilize addictive substances to escape or pull back from their low self-beliefs. Study by Munasinghe et al (2018), respondents who fill the Internet addiction test, meet the criteria for Internet addiction significantly have low self-esteem.…”
Section: Literature Review Self-esteemmentioning
confidence: 99%
“…State-of-the-art deep learning algorithms have achieved near-human-level accuracy in applications such as computer vision [24][25][26][27][28]. Nevertheless, one challenge remains for these algorithms when faced with inadequate amounts in acquiring adequate amounts of labeled data [29].…”
Section: Introductionmentioning
confidence: 99%